On the comparison of structural properties of as-prepared and thermally treated Mg-Zn nanoferrite powders synthesized via honey assisted sol-gel auto combustion - P. Tiwari; S S Modak; A R Tanna; S I Kundalwal; S N Kane (Next Research, 2026)

Upper limits of CH4 and OCS in the Martian atmosphere from NOMAD/TGO solar occultation: A study of vertical averaging and systematic uncertainties - M. Escudero-Jiménez; M.A. López-Valverde; J. Peralta; T. Moya; A. Belmonte; A. Brines; I. Thomas; G. Villanueva; G. Liuzzi; E. Knutsen; S. Viscardy; F. González-Galindo; et al. (Icarus, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Synthesis of 6‐bromo‐7‐arylaminoisoquinoline‐5,8‐quinones and its effects on Piscirickettsia salmonis infection in vitro - Juana A. Ibacache; Mario Espinoza; Paz Basualto‐Díaz; Victoria Pinto; Brenda Modak; Paula Zapata; Beatriz Valenzuela (Journal of Fish Diseases, 2024)
Among the most important aquaculture resources for our country, salmon and trout stand out. Their production has increased significantly in recent decades, making them two of the most valuable resources in economic terms. However, high aquaculture production has allowed many pathogens to proliferate, causing infectious diseases and significant production losses. Piscirickettsia salmonis is a gram‐negative, facultative intracellular bacterium that is responsible for causing severe disease in a variety of salmonid fish species. Despite the significant impact of P. salmonis on aquaculture, effective treatments for this disease remain limited. Current prevention and control strategies often include antibiotics and vaccines. However, these treatments have shown varying degrees of efficacy. A promising approach involves synthesizing bioactive analog compounds with antibacterial properties. Quinones, secondary metabolites that are abundant in nature, have become a focal point of interest due to their diverse physiological activities, including antibiotic, insecticidal, antifungal, and anticancer properties. In this study, it is shown the synthesis of series 6‐bromo‐7‐arylaminoisoquinoline‐5,8‐quinones, the characterization of these compounds using classical spectroscopic methods such as one‐dimensional nuclear magnetic resonance (NMR), FT‐IR (infrared), mass spectrometry, and the biological activity against Piscirickettsia salmonis. The brominated derivative compounds showed no cytotoxicity at any concentration evaluated. Furthermore, the infectivity of P. salmonis after treatment with the analog compounds indicated that derivatives methyl 6‐bromo‐7‐((4‐methoxyphenyl)amino)‐1,3‐dimethy‐5,8‐dioxo‐5,8‐dihydroisoquinoline‐4‐carboxylate ( 4b ) and methyl 7‐((4′‐amino‐[1,1′‐biphenyl]‐4‐yl)amino)‐6‐bromo‐1,3‐dimethy‐5,8‐dioxo‐5,8‐dihydroisoquinoline‐4‐carboxylate ( 4g ) reduced the bacterial load at 25 μg/mL concentration.

Emergence of two distinct variants of SARS-CoV-2 and an explosive second wave of COVID-19: the experience of a tertiary care hospital in Pune, India - Shubham Shrivastava; Suhas T. Mhaske; Meera S. Modak; Rashmi G. Virkar; Shamburaje S. Pisal; Akhilesh Chandra Mishra; Vidya A. Arankalle (Archives of Virology, 2022)

Comparative expression analysis of defense-related genes in both transgenic and nontransgenic Brassica juncea (var.) Varuna harbouring overexpressed MAPK3 gene in response to infection by Albugo candida - Annayasa Modak; Brij Raj Singh; Ashutosh Dubey; A. K. Tewari; Gohar Taj (Journal of Crop Science and Biotechnology, 2022)

Continuous decolorization of dye solution by homogeneous Fenton process in a rotating packed bed reactor - J. B. Modak; A. Bhowal; S. Datta; S. Karmakar (International Journal of Environmental Science and Technology, 2020)

Differential susceptibility of chick and mouse islets to streptozotocin and its co-relation with islet antioxidant status - Manisha A. Modak; Savita P. Datar; Ramesh R. Bhonde; Saroj S. Ghaskadbi (Journal of Comparative Physiology B, 2007)

Effect of certain socio-ecological factors on the population density of house dust mites in mattress-dust of asthmatic patients of Calcutta, India - A. Modak; G.K. Saha (Aerobiologia, 2002)